2017
DOI: 10.1002/mana.201600273
|View full text |Cite
|
Sign up to set email alerts
|

On null sequences for Banach operator ideals, trace duality and approximation properties

Abstract: Let scriptA be a Banach operator ideal and X be a Banach space. We undertake the study of the vector space of scriptA‐null sequences of Carl and Stephani on X, c0,Afalse(Xfalse), from a unified point of view after we introduce a norm which makes it a Banach space. To give accurate results we consider local versions of the different types of accessibility of Banach operator ideals. We show that in the most common situations, when scriptA is right‐accessible for (ℓ1;X), c0,Afalse(Xfalse) behaves much alike c0fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…This question was already answered for particular A-compact sets in several papers, see [2,7,8,9,11] among others. Our objective is to study the above problem for a wide class of A-compact sets.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…This question was already answered for particular A-compact sets in several papers, see [2,7,8,9,11] among others. Our objective is to study the above problem for a wide class of A-compact sets.…”
mentioning
confidence: 98%
“…In [11,Proposition 1.8], it was shown that A-compact sets are determined by operators in A with domain in 1 . Since Theorems 2.4 and 2.5 involve A-compact sets determined by operators with domain c 0 , we make a brief discussion of this type of compact sets in Section 1.…”
mentioning
confidence: 99%
See 3 more Smart Citations